The effect of Tyrophagus putrescentiae on Fusarium poae transmission and fungal community in stored barley in a laboratory experiment - Hubert, Jan; Nesvorná, Marta; Kopecký, Jan (Insect science, 2014)
The effect of Tyrophagus putrescentiae on Fusarium poae transmission and fungal community composition was studied in nonsterile barley grain. The experiments included following treatments: control barley without mites; barley containing 10 or 50 mites without preincubation on F. poae (Tp10 and Tp50); barley containing 10 or 50 mites after preincubation on F. poae (FTp10 and FTp50). The number of mites, successful transfer of F. poae, and changes in the fungal communities were examined after 21 d of experiment. Increase of deoxynivalenol (DON) content in the barley was chosen as a criterion of successful F. poae transfer. The preincubation of T. putrescentiae on F. poae increased DON level approximately to 800 and 300 μg/kg of grain for FTp10 and FTp50, respectively. T. putrescentiae population growth in FTp10 was lower than in Tp10, while no difference was found between FTp50 and Tp50. Fungal communities were compared by amplification, cloning and sequencing of ITS fragments, and operational taxonomic units (OTU) analysis. The OTU analysis did not support the transfer of F. poae via mites. From the analyzed clones, only 13 cloned sequences clustered with F. poae in an OTU defined at distance level 0.07. The related clones originated from FTp10, Tp10, Tp50 and control treatments, but not from FTp50. However, the presence of F. poae in FTp50 was confirmed by PCR amplification with specific primers. The observation may be explained by different effect of mite population density, that is, in the high density, (FTp50 treatment) the fungus was overgrazed, while the lower population density (FTp10) supported F. poae transfer.
Keywords: Fusarium poae; Animals; Food Storage; trichotheceny; semena rostlinná; mycotoxin; barley; Food Contamination; storage; Fusarium; skladování potravin; Trichothecenes; ječmen (rod); zvířata; Hordeum; kontaminace potravin; mykotoxiny; Seeds; deoxinivalenol (DON); Acaridae; mites; Mycotoxins